قياس مدى تقبل أعضاء هيئة التدريس بالجامعات الليبية لاستخدام تقنيات التدريس عن بعد باستخدام نموذج تقبل التكنولوجيا "TAM" - الشريف، طارق عبدالحفيظ; الفايدي، عبدالحفيظ عبدالسلام; المغربي، فيصل محمود (جامعة بنغازي - كلية الاقتصاد - قسم المحاسبة, 2021)
من أهم معايير نجاح استخدام تقنيات التدريس عن بعد هو رضى مستخدميها وتقبلهم لها؛ وعليه فقياس معدلات الرضى هو ليس لمجرد التعرف على التفاعل الحاصل بين التقنيات المقدمة ومستخدميها، بل للنظر بعمق إلى بعض العوامل السلوكية التي تؤثر على مدى تقبل هؤلاء المستخدمين لهذه التقنيات، ووفقا لمدى تأثير هذه العوامل تحدد المؤسسات المزودة والداعمة لهذه التقنيات مقدار ومعدلات استخدامها وحجم الإنفاق عليها، وهدف هذا البحث إلى قياس مدى تقبل أعضاء هيئة التدريس بالجامعات الليبية لاستخدام تقنيات التدريس عن بعد. ولتحقيق ذلك، تم الاعتماد على مجموعة من العوامل السلوكية كسهولة الاستخدام المدركة وفائدة الاستخدام المدركة. هذه العوامل وغيرها، قد ترتبط أيضا بعوامل أخرى خارجية كالدعم الفني والفروقات الفردية بين المستفيدين، ويتكون مجتمع البحث من أعضاء هيئة التدريس العاملين بالجامعات الليبية. وتم اختيار 330 استبانة من أصل 385 كعينة ممثلة لمجتمع البحث، واشتملت الاستبانة الموزعة على عوامل مختلفة لقياس مدى تقبل أعضاء هيئة التدريس لتقنيات التدريس عن بعد. ولاختبار الفرضيات الخاصة بالبحث استخدم برنامج (Smart PLS-SEM). وأكدت نتائج البحث أن الدعم الفني له تأثير مباشر فقط على سهولة الاستخدام المدركة، وليس له أي تأثير على الفائدة المدركة ولا على المواقف تجاه التقنية، وأهم ما توصل إليه البحث كنتيجة رئيسية هو أن أعضاء هيئة التدريس المشاركين في الدراسة رغم إدراكهم لسهولة وفائدة استخدام تقنيات التدريس عن بعد، إلا أنهم قد يصبحون مترددين في استخدام تلك التقنيات بسبب مجموعة من المعوقات التي تشكل حاجزا بينهم وبين استخدام تقنيات التدريس عن بعد. One of the most important criteria for the success of using distance teaching techniques is the satisfaction and acceptance of its users to it. Accordingly, measuring satisfaction rates is not just to identify the interaction between the provided technologies and their users, but to look in-depth at some of the behavioral factors that affect the extent to which these users accept these technologies. According to the impact of these factors, the organizations that provide and support these technologies determine the amount and rates of their use and the amount of spending on them. The aim of this research is to measure the extent to which faculty members in Libyan universities accept the use of distance teaching techniques. To achieve this, a set of behavioral factors such as perceived ease of use and perceived usefulness of use were relied on. These and other factors may also be linked to other external factors such as technical support and individual differences between the beneficiaries. The research population consists of faculty members working in Libyan universities. 330 questionnaire sheets were selected out of 385 as a representative sample, and the distributed questionnaire included various factors to measure the extent to which faculty members accept distance teaching techniques. And to test the hypotheses of the research, the program (Smart PLS-SEM) was used. The results of the research confirmed that technical support has a direct effect only on perceived ease of use and has no effect on perceived usefulness nor on attitudes towards technology. The most important finding of the research as the main result is that the faculty members participating in the study, despite their awareness of the ease and usefulness of using distance teaching techniques, may become reluctant to use these techniques because of a set of obstacles that constitute a barrier between them and the use of distance teaching techniques.
Keywords: التعليم الجامعي -- التدريس عن بعد -- أعضاء هيئة التدريس -- الجامعات الليبية